GAYA KEPEMIMPINAN KEPALA PUSKESMAS - Marwanto, I Gusti Gede Heru (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2019)
The various ways motivate the research in this thesis that the leader moves his subordinates to achieve the goals of the organization, in the end, must also be able to generate performance from his assistants. Indirectly leadership also determines the formation of employee performance. The better one's direction toward subordinates, the higher the performance of their subordinates. This type of research is qualitative research, based on the discussion including descriptive analysis. The results of the study were: 1) The implementation of the behavior of the head was concerned with the task indicated by the deliberation principles. That was carried out in the morning brainstorming and internally with the programmers of each activity. That increases the discipline of work time to meet the performance targets. Head Puskesmas has the authority of the health department and must be carried out by subordinates or staff, prioritizing the cooperation relationship shown by all employees at the Pandean health center given responsibility in carrying out health programs in the Pandean health center, and emphasizing the results achieved that can improve employee performance. 2) The dominant factor in implementing the leadership style of the Head of Community Health Center at Pandean Health Center Dongko District is not necessarily democratic, but situational, this leadership style gives responsibility and authority to all parties, so that they are actively involved in the organization, members are given the opportunity to provide suggestions and suggestions and criticism for the betterment of the organization.